(untitled) (Academicia Globe: Inderscience Research, 2023)
The aim of the present review was to describe the most commonly observed changes of periodontal and gingiva changes happened because of orthodontic treatment in order to facilitate collaboration between periodontal diseases and orthodontic treatment. An electric data base used to carried out by using google scholar abstract and citation data base and bibliographic material. In this review we discussed the effect of orthodontic treatment on soft tissues. In the conclusion, the importance of maintenance on the health of the patients’ gingiva was a priority during orthodontic treatment